Preparation method of high-durability multifunctional super-hydrophobic coating

Through the methods of non-solvent-induced phase separation and nanotube enhancement, a superhydrophobic coating with high durability and versatility was constructed, solving the problems of poor durability and single function of existing coatings, and achieving widespread application in multiple fields .

CN119242105APending Publication Date: 2025-01-03HEBEI UNIV OF TECH

Patent Information

Application Number
CN202411651271.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing superhydrophobic coatings have poor durability and single functions, which are prone to failure due to minor mechanical damage, and are difficult to widely use in many fields.

Method used

Through non-solvent induction, the mixed liquid of the adhesive and the hydrophobic modified nanoparticles are separated to form a uniform suspension, so that the nanoparticles are coated on the outer layer of the adhesive particles, and nanotubes are added to enhance the connection between the adhesive particles. Build a micro-nano hierarchical structure to improve the mechanical stability and functionality of the coating.

Benefits of technology

It achieves high durability, chemical stability, UV resistance and thermal stability, and imparts the coating with versatility such as photothermal, electric heating, antibacterial, easy to remove ice, and high thermal conductivity. It is suitable for various substrates and simplifies Large-scale preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242105A_ABST
    Figure CN119242105A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-durability multifunctional super-hydrophobic coating. According to the method, a mixed solution of an adhesive and hydrophobic modified nanoparticles is subjected to phase separation through non-solvent induction, so that the hydrophobic modified nanoparticles are coated on the outer layers of adhesive particles to form a uniform suspension, and finally, a micro-nano structure dispersed on the surface and inside of a coating can be obtained. After the surface layer is worn, the newly exposed surface still has an excellent micro-nano structure, namely super-hydrophobic performance; on the other hand, the nanotubes (wires) are added into the suspension, so that the mutual connection among the adhesive particles is further enhanced, and finally, the firm super-hydrophobic coating can be obtained. The super-hydrophobic coating provided by the invention has excellent durability, chemical stability, ultraviolet resistance and thermal stability, and functions of photo-thermal, electric heating, antibiosis, easy deicing, high thermal conductivity and the like, is suitable for various base materials, and is easy to realize large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of super hydrophobic coatings, and in particular relates to a method for preparing a highly durable multifunctional super hydrophobic coating. Background Art

[0002] Inspired by the unique wettability of natural surfaces such as lotus leaves, rice leaves and water striders, superhydrophobic coatings have gradually attracted widespread attention from researchers and engineers. Superhydrophobic coatings refer to surfaces with high contact angles (WCA ≥ 150°) and low rolling angles (WSA ≤ 10°) for water, so water droplets can easily roll off the coating surface. The unique superhydrophobic properties of this coating give it many special functions, such as self-cleaning, anti-fouling, corrosion resistance, anti-icing, oil-water separation, anti-biological adhesion, fluid drag reduction, and water collection, so it shows great application prospects in many fields. However, the application of superhydrophobic coatings in actual production and life is still relatively limited, mainly due to its poor durability and single function. Slight mechanical damage may lead to the loss of superhydrophobicity, and the single functionality limits its application in the fields of antibacterial, anti-icing, and easy deicing.

[0003] It is a common method to construct a superhydrophobic surface based on hydrophobic nanoparticles. However, due to the small number of contact sites between nanoparticles and between particles and substrates, and the weak interaction force, nanoparticles are often difficult to stably adhere to the surface of the substrate. Therefore, the strategy of adding adhesives is usually adopted to enhance the adhesion between nanoparticles and substrates (Zhao Y, Huo M, Huo J, et al. Preparation of silica-epoxy superhydrophobic coatingwith mechanical stability and multifunctional performance via one-step approach [J]. Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2022, 653: 129957.), thereby improving the mechanical stability and durability of the coating. This strategy is simple, low-cost, and easy to prepare on a large scale. For example, in Chinese invention patent CN118440566A, epoxy resin E51, modified silica nanoparticles and curing agent are uniformly mixed in ethanol to obtain a SiO2@E51 suspension. Then, the suspension is evenly sprayed on the metal surface, and a superhydrophobic coating is obtained after curing. In this method, E51 epoxy resin acts as an adhesive to fix silica particles on the substrate, thereby enhancing the mechanical stability of the superhydrophobic coating. However, its durability is still not ideal, and the contact angle is less than 150° after 30 tape peelings.

[0004] Although adhesives can enhance the mechanical stability of coatings, they also tend to cause a large number of low-surface-energy nanoparticles to be embedded in the adhesive, leaving only a small number of particles on the surface of the coating. Since the nanoparticles have very low polarity and weak interaction between them, they are easy to fall off and "powder off", and the super-hydrophobicity of the coating is easily lost due to slight wear. Adding too much adhesive to increase the adhesion between particles will reduce the roughness of the coating surface and cause a sharp decrease in the hydrophobic effect. Therefore, it is relatively difficult to prepare a super-hydrophobic coating with excellent durability by simply mixing adhesives with nanoparticles.

[0005] In summary, the development of a multifunctional superhydrophobic coating with excellent mechanical stability and high durability is of great significance for its future large-scale practical application. Summary of the invention

[0006] The present invention aims to solve the problems of poor durability, easy failure and single function of super-hydrophobic coating in the prior art, and provides a method for preparing a super-hydrophobic coating with high durability and other functions. The method causes a mixed solution of an adhesive and hydrophobically modified nanoparticles to separate by non-solvent induction, so that the hydrophobically modified nanoparticles are coated in the outer layer of the adhesive particles to form a uniform suspension, and finally a micro-nano structure dispersed on the surface and inside of the coating can be obtained, and the newly exposed surface after the surface layer is worn still has excellent micro-nano structure, i.e., super-hydrophobic performance; on the other hand, by adding nanotubes (wires) to the suspension, the interconnection between the adhesive particles is further enhanced, and finally a firm super-hydrophobic coating can be obtained. At the same time, the introduced functional nanotubes (wires) can also increase the functionality of the super-hydrophobic coating. The super-hydrophobic coating of the present invention has excellent durability, chemical stability, UV resistance and thermal stability, as well as photothermal, electric heating, antibacterial, easy deicing, high thermal conductivity and other functionalities, is suitable for various substrates, and is easy to achieve large-scale preparation.

[0007] The technical solution of the present invention: A method for preparing a highly durable multifunctional super-hydrophobic coating, the method comprising the following steps: (1) Hydrophobic modification of nanoparticles: The nanoparticles are dispersed in anhydrous ethanol, and after being dispersed evenly by ultrasonication and stirring, ammonia water, deionized water, and silane coupling agent are added dropwise during stirring, and then reacted at 25-45°C for 7-14 hours. The reaction product is centrifuged, washed with anhydrous ethanol for 1-3 times, and dried to obtain hydrophobically modified nanoparticles. Among them, 15-25 g of nanoparticles are added to every 1 L of anhydrous ethanol; the mass ratio of each component is nanoparticles: ammonia water: deionized water: silane coupling agent = 10: 0.1-0.4: 0.5-1: 1-5; The mass percentage concentration of the ammonia water is 25-28%; (2) Preparation of super-hydrophobic coating: dissolving an adhesive in a good solvent, adding hydrophobically modified nanoparticles to the adhesive solution, and uniformly dispersing the adhesive by ultrasonication and stirring. Then, adding a poor solvent for the adhesive dropwise under stirring to induce phase separation of the adhesive. Finally, dispersing the nanotubes (wires) into the above suspension to obtain a super-hydrophobic coating. The mass ratio of each component is as follows: adhesive: hydrophobically modified nanoparticles: nanotubes (wires): good solvent: poor solvent = 1: 0.2~2: 0.05~0.5: 5~50: 5~50; (3) Preparation of a highly durable multifunctional super-hydrophobic coating: The super-hydrophobic coating obtained in step (2) is sprayed onto a substrate material with a spraying thickness of 10 to 200 μm, and then the coating is placed at 30 to 150° C. for 12 to 36 h to obtain a highly durable multifunctional super-hydrophobic coating.

[0008] The nanoparticles in step (1) are one or more of silicon dioxide, titanium dioxide, zirconium dioxide, diatomaceous earth, attapulgite, and zinc oxide.

[0009] The diameter of the nanoparticles in step (1) is 5 to 100 nm.

[0010] The silane coupling agent in step (1) is one or more of methyltrimethoxysilane, octyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, perfluorooctyltrimethoxysilane or perfluorooctyltriethoxysilane.

[0011] The adhesive in step (2) is one or more of styrene-butadiene rubber, styrene-butadiene-styrene triblock copolymer (SBS), hydrogenated styrene-butadiene block copolymer (SEBS), chloroprene rubber, alkyd resin, fluorocarbon resin, epoxy resin, epoxy-modified silicone resin, acrylic modified silicone resin, polyester modified silicone resin, alkyd modified silicone resin, epoxy resin, polyurethane or polydimethylsiloxane.

[0012] In step (2), the good solvent is ethyl acetate, butyl acetate, ethanol, tetrahydrofuran or xylene.

[0013] In the step (2), when the good solvent is ethyl acetate or butyl acetate, the poor solvent is methanol, ethanol or isopropanol; when the good solvent is ethanol or tetrahydrofuran, the poor solvent is water; when the good solvent is xylene, the poor solvent is methanol, ethanol or isopropanol.

[0014] The nanotubes (wires) in step (2) are one or more of carbon nanotubes, boron nitride nanotubes, polymer nanotubes, halloysite nanotubes, zinc oxide nanowires, iron oxide nanowires, silver nanowires, titanium oxide nanowires, and silicon carbide nanowires.

[0015] In step (3), the substrate material is plastic, glass, metal, wood, ceramic, interior or exterior wall of a building or textile.

[0016] The essential features of the present invention are: Most of the current super-hydrophobic coatings are prepared by simply mixing hydrophobic nanoparticles with adhesives and spraying them on the substrate. The defect is that the surface of the super-hydrophobic coating prepared by this method is relatively flat, a large number of hydrophobic nanoparticles are embedded in the adhesive, the coating is very compact, and only a small number of hydrophobic nanoparticles are distributed on the surface of the coating. At this time, slight wear will cause the nanoparticles to fall off, the coating surface becomes smoother, and the super-hydrophobicity will be lost. For super-hydrophobic coatings, the roughness of the surface has a great impact on the performance of the coating. The rougher the coating surface, the better the performance.

[0017] In the present invention, polymer adhesive can be induced by non-solvent phase separation to form mutually separated spherical aggregates, and low surface energy nanoparticles are wrapped in the surface of these adhesive aggregates. When the suspension is sprayed onto the substrate surface, the coating is formed after the solvent evaporates, and the spherical aggregates formed by phase separation build microstructures on the coating surface, and at the same time, the low surface energy nanoparticles wrapped in the adhesive aggregate surface form nanostructures. These two structures jointly constitute a micro-nano hierarchical structure, and this low surface energy micro-nano hierarchical structure has excellent super-hydrophobic properties, and the hierarchical micro-nano structure constructed is not only present in the coating surface, but also extends to the coating interior. This means that even if the surface is damaged, the exposed new surface can still maintain good super-hydrophobic performance. This strategy helps to effectively retain low surface energy nanoparticles on the coating surface with micro-nano structure, so it is possible to prepare a high durability multifunctional super-hydrophobic coating.

[0018] In addition, considering that the low surface energy nanoparticles on the surface of the adhesive spherical aggregates may weaken the mutual adhesion between the aggregates, thereby affecting the overall mechanical stability of the coating. Therefore, nanotubes (wires) are added to the formed phase separation suspension. Since the adhesive, nanoparticles and solvent are in a heterogeneous state at this time, the added nanotubes (wires) are easily dispersed evenly in the suspension. After the coating is formed, the nanotubes (wires) are distributed in the coating in the form of a skeleton, effectively connecting the adhesive aggregates, thereby improving the overall mechanical stability of the coating. At the same time, due to the functionality of nanotubes (wires) such as carbon nanotubes, boron nitride nanotubes, and zinc oxide nanowires, the super-hydrophobic coating can also be given excellent photothermal, electrothermal, high thermal conductivity, easy deicing, antibacterial and other functions, further broadening the application field of super-hydrophobic coatings.

[0019] The beneficial effects of the present invention are: (1) The non-solvent-induced phase separation of the adhesive can effectively prevent the hydrophobically modified nanoparticles from being embedded in the adhesive. By simple spraying, a micro-nano hierarchical structure can be constructed on the surface of various substrates. The prepared coating has excellent superhydrophobic properties, with a water contact angle greater than 165° and a water rolling angle less than 2°.

[0020] (2) Nanotubes (wires) can be tightly combined with adhesives due to their large aspect ratio and specific surface area, and are distributed in the coating in the form of a skeleton. This structure can give the coating excellent mechanical stability and durability. The mechanical stability and durability of the coating were tested using the method in GB / T1768-2006. The prepared superhydrophobic coating still had excellent superhydrophobic properties after 500 cycles of Taber abrasion (grinding wheel model CS-10) under a load of 500 g. The test was carried out using the tape stripping method. The tape (model Scotch 3M 810) was adhered to the surface of the coating sample and pressed tightly. A weight of 50 g was placed on the surface and rolled back and forth slowly. The tape was then quickly torn off and peeled off. After 150 times of tape stripping, it still had excellent superhydrophobic properties.

[0021] (3) The super-hydrophobic coating prepared by the present invention has excellent chemical stability and shows extremely high resistance to common corrosive liquids and liquids commonly used in daily life. After immersion in pH=1, pH=7, pH=14, and 0.1 M sodium chloride solution for 48 h, the contact angle of the coating is still greater than 150° and the rolling angle is still less than 10°.

[0022] (4) The super-hydrophobic coating prepared by the present invention has excellent UV resistance. When the coating is placed in a UV aging box at an ambient temperature of 60°C, after irradiation with ultraviolet rays of wavelength 315-400 nm for 300 h, the contact angle of the super-hydrophobic coating is still greater than 150° and the rolling angle is still less than 10°. Since the intensity of ultraviolet radiation is several times that of sunlight, it is shown that the super-hydrophobic coating of the present invention can be used outdoors.

[0023] (5) The super-hydrophobic coating prepared by the present invention has excellent thermal stability. After the coating is placed in an oven at 100°C for 300 h, the contact angle of the super-hydrophobic coating is still greater than 150° and the rolling angle is still less than 10°.

[0024] (6) The preparation process of the present invention adopts a one-step spraying method, which has a simple operation process and is not limited by the substrate. It is suitable for the surfaces of substrates of different materials such as metal materials, synthetic polymer materials, natural polymer materials, inorganic non-metallic materials, etc.

[0025] (7) The present invention can give the super-hydrophobic coating excellent photothermal, electrothermal, high thermal conductivity, easy deicing, antibacterial and other functions by adding different nanotubes (wires).

[0026] (8) The super-hydrophobic coating of the present invention can be prepared on a large scale and in batches, which reduces the cost and improves the efficiency. This is of great significance for promoting the practical application of super-hydrophobic coatings in various fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1: Static contact angle test photo of the super-hydrophobic coating in Example 1; Figure 2 : Test photos of the self-cleaning function of the super-hydrophobic coating in Example 1; Figure 3 : Test photos of the antifouling function of the super-hydrophobic coating in Example 1; Figure 4 : Photos of the super-hydrophobic coating applied on substrates of different materials in Example 1; Figure 5 : The contact angle and rolling angle of the super-hydrophobic coating on the substrate materials of different materials in Example 1; Figure 6 : Changes in contact angle and rolling angle of the superhydrophobic coating in Example 1 with the number of Taber abrasion cycles; Figure 7 : Changes in contact angle and rolling angle of the super-hydrophobic coating in Example 1 with the number of tape stripping times; Figure 8 : Changes in contact angle and sliding angle of the super-hydrophobic coating in Example 1 with heat treatment time; Fig. 9 : Changes in contact angle and rolling angle of the superhydrophobic coating in Example 1 with ultraviolet irradiation time. DETAILED DESCRIPTION

[0028] In order to help other technical personnel in the field better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be described in detail and clearly below. The embodiments are only a part of the present application, not all embodiments. On this basis, any other embodiments obtained by any ordinary technician without performing creative work should be deemed to be within the scope of protection of this application.

[0029] Embodiment 1: (1) Hydrophobic modification of nanoparticles: 20 g of silica nanoparticles (10-20 nm in diameter) were dispersed in a beaker containing 1 L of anhydrous ethanol. The beaker was placed in an ultrasonic cleaner and ultrasonically treated at 300 W for 30 min. The reaction system was transferred to a reactor equipped with a mechanical stirrer and stirred until the silica nanoparticles were evenly dispersed. During the stirring process, 1.08 g of deionized water, 0.34 g of ammonia water (28%) and 8 g of perfluorodecyltrimethoxysilane (98%) were added to the reactor in sequence. The reaction was then carried out at 25 °C for 12 h. The reaction product was centrifuged, washed three times with anhydrous ethanol and dried to obtain hydrophobically modified silica nanoparticles. (2) Preparation of super-hydrophobic coating: 5 g of fluorocarbon resin was completely dissolved in 70 g of butyl acetate, and then 4 g of hydrophobically modified silica nanoparticles obtained in the previous step were added to the above solution. After being dispersed evenly by ultrasonication and stirring, 30 g of anhydrous ethanol was added dropwise during stirring to induce phase separation of the fluorocarbon resin. Finally, 0.3 g of carbon nanotubes was dispersed in the above suspension to prepare a super-hydrophobic coating. (3) Preparation of a highly durable multifunctional super-hydrophobic coating: The super-hydrophobic coating obtained in step (2) is sprayed on a substrate material, wherein the substrate material is polymethyl methacrylate (PMMA) and the spraying thickness is 50 μm. The coating is then placed at 80° C. for 24 h to obtain a highly durable multifunctional super-hydrophobic coating. In order to test the applicability of superhydrophobic coatings on substrates of different materials, highly durable multifunctional superhydrophobic coatings were prepared on substrates of iron, copper, aluminum, polyurethane (PU), polypropylene (PP), rubber, polyvinyl chloride (PVC), polyethylene terephthalate (PET), wood, bamboo, paper, marble, cement board, and glass. The other steps were the same as above.

[0030] Figure 1 The contact angle (168.7°) of the super-hydrophobic coating prepared on the PMMA surface was measured using a KRÜSS model DSA30 optical contact angle meter, proving that the coating has super-hydrophobic properties.

[0031] Figure 2 This is the test process of the self-cleaning function of the super-hydrophobic coating. The sample is tilted 15°, 2 g of silica powder is sprinkled on the sample surface, and water is dripped on the sample. It can be seen from the photo that when the water droplets come into contact with the coating surface with sand, the water droplets immediately roll down and take away the sand, making the surface clean and tidy. This process shows that the super-hydrophobic coating has excellent self-cleaning ability.

[0032] Figure 3 This is the test process of the antifouling function of the super-hydrophobic coating. The sample with half sprayed with the super-hydrophobic coating and the other half not sprayed was immersed in water dyed with ink, and the sample was taken out after 30 seconds. From the photo, it can be seen that the surface of the super-hydrophobic coating is still very clean, while the surface of the sample not sprayed is stained with sewage. This process proves that the super-hydrophobic coating has excellent antifouling performance.

[0033] Figure 4 This is a photo of a highly durable multifunctional super-hydrophobic coating prepared on substrates of different materials through a one-step spraying method.

[0034] Figure 5The super-hydrophobic coatings on the surfaces of different substrates were tested, and it was found that the contact angles of the super-hydrophobic coatings were all greater than 165° and the rolling angles were all less than 2°, proving that the super-hydrophobic coatings have excellent applicability.

[0035] Figure 6 The contact angle and rolling angle of the super-hydrophobic coating change with the number of Taber abrasion cycles in the process of testing the mechanical stability and durability of the coating using the method in GB / T 1768-2006. As shown in the figure, after 500 cycles of Taber abrasion (grinding wheel model is CS-10) under a load of 500 g, the contact angle of the coating is still greater than 150° and the rolling angle is still less than 10°, which fully demonstrates that the super-hydrophobic coating has excellent durability and mechanical stability.

[0036] Figure 7 The coating was tested by the tape stripping method. The tape (model: Scotch 3M 810) was stuck to the surface of the coating sample and pressed tightly. A weight of 50 g was placed on the surface and rolled slowly back and forth. The tape was then quickly torn off. The contact angle and rolling angle of the super-hydrophobic coating changed with the number of tape stripping times as shown in the figure. After 150 times of tape stripping, the contact angle of the coating was still greater than 150° and the rolling angle was still less than 10°, which fully demonstrated that the super-hydrophobic coating has excellent durability and mechanical stability.

[0037] Figure 8 When the coating is placed in an oven at 100°C for thermal stability testing, the contact angle and rolling angle of the super-hydrophobic coating change with the heat treatment time. As shown in the figure, after 300 hours of heat treatment, the contact angle of the super-hydrophobic coating is still greater than 150° and the rolling angle is still less than 10°, which fully demonstrates that the super-hydrophobic coating has excellent thermal stability.

[0038] Fig. 9 The coating is placed in a UV aging box at an ambient temperature of 60°C and irradiated with ultraviolet light of a wavelength of 315-400 nm. The contact angle and rolling angle of the super-hydrophobic coating change with the UV irradiation time. As shown in the figure, after 300 hours of irradiation, the contact angle of the super-hydrophobic coating is still greater than 150° and the rolling angle is still less than 10°, which fully demonstrates that the super-hydrophobic coating has excellent UV resistance.

[0039] Embodiment 2: (1) Hydrophobic modification of nanoparticles: 20 g of silica nanoparticles (10-20 nm in diameter) were dispersed in a beaker containing 1 L of anhydrous ethanol. The beaker was placed in an ultrasonic cleaner and ultrasonically treated at 300 W for 30 min. The reaction system was transferred to a reactor equipped with a mechanical stirrer and stirred until the silica nanoparticles were evenly dispersed. During the stirring process, 1.3 g of deionized water, 0.45 g of ammonia water (28%) and 7.5 g of perfluorooctyltrimethoxysilane were added to the reactor in sequence. The reaction was then carried out at 25 °C for 12 h. The reaction product was centrifuged, washed three times with anhydrous ethanol and dried to obtain hydrophobically modified silica nanoparticles. (2) Preparation of super-hydrophobic coating: 4 g of acrylic modified silicone resin was completely dissolved in 75 g of anhydrous ethanol, and then 3.5 g of hydrophobically modified silica nanoparticles obtained in the previous step were added to the above solution. After being dispersed evenly by ultrasonication and stirring, 25 g of deionized water was added dropwise during stirring to induce phase separation of acrylic modified silicone resin. Finally, 0.2 g of carbon nanotubes was dispersed in the above suspension to prepare a super-hydrophobic coating. (3) Preparation of a highly durable multifunctional super-hydrophobic coating: The super-hydrophobic coating obtained in step (2) is sprayed onto a substrate material made of aluminum with a spraying thickness of 70 μm. The coating is then placed at 100°C for 12 h to obtain a highly durable multifunctional super-hydrophobic coating.

[0040] Embodiment 3: (1) The hydrophobic modification of the nanoparticles is the same as step (1) of Example 1; (2) Preparation of super-hydrophobic coating: 5 g of SEBS was completely dissolved in 70 g of xylene, and then 6 g of hydrophobically modified silica nanoparticles obtained in the previous step were added to the above solution. After being dispersed evenly by ultrasonication and stirring, 30 g of anhydrous ethanol was added dropwise during stirring to induce phase separation of SEBS. Finally, 0.4 g of carbon nanotubes was dispersed in the above suspension to prepare a super-hydrophobic coating. (3) Preparation of a highly durable multifunctional super-hydrophobic coating: The super-hydrophobic coating obtained in step (2) is sprayed on a substrate material made of PP with a spraying thickness of 100 μm. The coating is then placed at 40°C for 12 h to obtain a highly durable multifunctional super-hydrophobic coating.

[0041] Embodiment 4: (1) The hydrophobic modification of the nanoparticles is the same as step (1) of Example 1; (2) Preparation of super-hydrophobic coating: 4 g of epoxy resin was completely dissolved in 50 g of butyl acetate, and then 5 g of hydrophobically modified silica nanoparticles obtained in the previous step were added to the above solution. After being dispersed evenly by ultrasonication and stirring, 30 g of anhydrous ethanol was added dropwise during stirring to induce phase separation of the epoxy resin. Finally, 0.25 g of carbon nanotubes was dispersed in the above suspension to prepare a super-hydrophobic coating. (3) Preparation of a highly durable multifunctional super-hydrophobic coating: The super-hydrophobic coating obtained in step (2) is sprayed onto a substrate material made of wood with a spraying thickness of 80 μm. The coating is then placed at 80°C for 12 h to obtain a highly durable multifunctional super-hydrophobic coating.

[0042] Embodiment 5: (1) The hydrophobic modification of the nanoparticles is the same as step (1) of Example 1; (2) Preparation of super-hydrophobic coating: 4 g of SEBS was completely dissolved in 65 g of butyl acetate, and then 5 g of hydrophobically modified silica nanoparticles obtained in the previous step were added to the above solution. After being dispersed evenly by ultrasonication and stirring, 35 g of anhydrous ethanol was added dropwise during stirring to induce phase separation of SEBS. Finally, 0.3 g of zinc oxide nanowires was dispersed in the above suspension to prepare a super-hydrophobic coating. (3) Preparation of a highly durable multifunctional super-hydrophobic coating: The super-hydrophobic coating obtained in step (2) is sprayed onto a substrate material made of iron with a spraying thickness of 100 μm. The coating is then placed at 40°C for 12 h to obtain a highly durable multifunctional super-hydrophobic coating.

[0043] The present invention only requires adding a poor solvent for the adhesive to the mixed liquid during the stirring process to separate the adhesive phase. At this time, the coating prepared by spraying the suspension onto the substrate will be greatly improved in durability. Secondly, some nanotubes (wires) with a large aspect ratio are added to the coating. Just like composite materials such as reinforced concrete, the nanotubes (wires) can play a reinforcing role and make the mechanical stability of the coating better. In addition, these nanotubes (wires) can also increase the functionality of the coating. For example, adding carbon nanotubes can make the coating heat up faster under light, so that the ice layer can be removed faster in winter.

[0044] It can be seen that the present invention can greatly improve the durability of the super-hydrophobic coating without increasing the complexity of the preparation too much. After using the technology of the present invention, a hierarchical micro-nano rough structure can be constructed on the surface and inside of the coating. At this time, even if a layer of the surface is worn away, the exposed new surface still has a good micro-nano rough structure, the super-hydrophobic performance is still very excellent, and the durability is greatly improved.

[0045] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing a highly durable multifunctional super-hydrophobic coating, characterized in that The method comprises the following steps: (1) Hydrophobic modification of nanoparticles: The nanoparticles are dispersed in anhydrous ethanol, dispersed by ultrasonication and stirring, and then ammonia water, deionized water, and a silane coupling agent are added dropwise during stirring. The mixture is then reacted at 25-45°C for 7-14 h. The reaction product is centrifuged, washed with anhydrous ethanol for 1-3 times, and dried to obtain hydrophobically modified nanoparticles. Among them, 15-25 g of nanoparticles are added to every 1 L of anhydrous ethanol; the mass ratio of each component is nanoparticles: ammonia water: deionized water: silane coupling agent = 10: 0.1-0.4: 0.5-1: 1-5; The nanoparticles in step (1) are one or more of silicon dioxide, titanium dioxide, zirconium dioxide, diatomaceous earth, attapulgite, and zinc oxide; (2) Preparation of super-hydrophobic coating: dissolving an adhesive in a good solvent, adding hydrophobically modified nanoparticles to the adhesive solution, and uniformly dispersing the adhesive by ultrasonication and stirring. Then, adding a poor solvent for the adhesive dropwise under stirring to induce phase separation of the adhesive. Finally, dispersing the nanotubes (wires) into the above suspension to obtain a super-hydrophobic coating. The mass ratio of each component is as follows: adhesive: hydrophobically modified nanoparticles: nanotubes (wires): good solvent: poor solvent = 1: 0.2~2: 0.05~0.5: 5~50: 5~50; (3) Preparation of a highly durable multifunctional super-hydrophobic coating: The super-hydrophobic coating obtained in step (2) is sprayed onto a substrate material with a spraying thickness of 10 to 200 μm, and then the coating is placed at 30 to 150° C. for 12 to 36 h to obtain a highly durable multifunctional super-hydrophobic coating.

2. The method for preparing a highly durable multifunctional super-hydrophobic coating as claimed in claim 1, characterized in that The diameter of the nanoparticles in step (1) is 5 to 100 nm.

3. The method for preparing a highly durable multifunctional super-hydrophobic coating as claimed in claim 1, characterized in that the mass percentage concentration of the ammonia water is 25-28%.

4. The method for preparing a highly durable multifunctional super-hydrophobic coating according to claim 1, characterized in that The silane coupling agent in step (1) is one or more of methyltrimethoxysilane, octyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, vinyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorodecyltriethoxysilane, perfluorooctyltrimethoxysilane or perfluorooctyltriethoxysilane.

5. The method for preparing a highly durable multifunctional super-hydrophobic coating as claimed in claim 1, characterized in that The adhesive in step (2) is one or more of styrene-butadiene rubber, styrene-butadiene-styrene triblock copolymer (SBS), hydrogenated styrene-butadiene block copolymer (SEBS), chloroprene rubber, alkyd resin, fluorocarbon resin, epoxy resin, epoxy-modified silicone resin, acrylic modified silicone resin, polyester modified silicone resin, alkyd modified silicone resin, epoxy resin, polyurethane or polydimethylsiloxane.

6. The method for preparing a highly durable multifunctional super-hydrophobic coating according to claim 1, characterized in that In step (2), the good solvent is ethyl acetate, butyl acetate, ethanol, tetrahydrofuran or xylene; In the step (2), when the good solvent is ethyl acetate or butyl acetate, the poor solvent is methanol, ethanol or isopropanol; when the good solvent is ethanol or tetrahydrofuran, the poor solvent is water; when the good solvent is xylene, the poor solvent is methanol, ethanol or isopropanol.

7. The method for preparing a highly durable multifunctional super-hydrophobic coating according to claim 1, characterized in that The nanotubes (wires) in step (2) are one or more of carbon nanotubes, boron nitride nanotubes, polymer nanotubes, halloysite nanotubes, zinc oxide nanowires, iron oxide nanowires, silver nanowires, titanium oxide nanowires, and silicon carbide nanowires.

8. The method for preparing a highly durable multifunctional super-hydrophobic coating according to claim 1, characterized in that In step (3), the substrate material is plastic, glass, metal, wood, ceramic, interior or exterior wall of a building or textile.

Citation Information

Patent Citations

  • Wear-resisting super-hydrophobic coating composition as well as preparation method and application thereof

    CN107987675A

  • High-durability environment-friendly super-hydrophobic composite coating and preparation method thereof

    CN114015259A

  • Method for preparing stable super-hydrophobic surface on complex modeling base material at super-fast speed

    CN114773921A

Cited By

  • Preparation method of high-stability super-hydrophobic composite material of flexible armor structure for metal corrosion prevention

    CN120054841A

  • A method for preparing a highly stable superhydrophobic composite material with a flexible armor structure for metal corrosion protection

    CN120054841B

  • Preparation method of micro-nano graded super-hydrophobic coating

    CN120394319A

  • Preparation method of micro-nano hierarchical super-hydrophobic coating

    CN120394319B

  • Preparation and application of super-hydrophobic film material

    CN120904499A